2017
DOI: 10.3390/f8020040
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of Soil Respiration in Experimental Tree Plantations in Lowland Costa Rica

Abstract: Abstract:The principal objective of this study was to determine if there is consistent temporal variability in soil respiration from different forest plantations in a lowland tropical rainforest environment. Soil respiration was measured regularly over 2004 to 2010 in replicated plantations of 15-to 20-year-old evergreen tropical trees in lowland Costa Rica. Statistically significant but small differences in soil respiration were observed among hours of the day; daytime measurements were suitable for determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 76 publications
1
18
0
1
Order By: Relevance
“…In addition, although small in magnitude, their observed diel patterns were apparently driven by fluctuations in soil moisture rather than temperature (Rubio & Detto, 2017). Other studies have found relationships with soil temperature similar to ours (Meir et al, 1996; Raich, 2017; Zanchi et al, 2014), although hysteresis was also evident suggesting other potential controls in addition to temperature on diel variation of soil respiration (Raich, 2017; Rubio & Detto, 2017; Vargas & Allen, 2008a; Zanchi et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, although small in magnitude, their observed diel patterns were apparently driven by fluctuations in soil moisture rather than temperature (Rubio & Detto, 2017). Other studies have found relationships with soil temperature similar to ours (Meir et al, 1996; Raich, 2017; Zanchi et al, 2014), although hysteresis was also evident suggesting other potential controls in addition to temperature on diel variation of soil respiration (Raich, 2017; Rubio & Detto, 2017; Vargas & Allen, 2008a; Zanchi et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Our high frequency measurements using automated chambers revealed significant diel variation of soil respiration in this tropical moist forest throughout a 3‐year period. Results from prior studies investigating soil respiration on this time scale in other tropical forests have been mixed, with some studies reporting significant diel variation of soil respiration (Lugo et al, 2008; Medina, 1969; Medina et al, 1980; Meir et al, 1996;Raich, 2017 ; Rubio & Detto, 2017 ; Vargas & Allen, 2008a ; Zanchi et al, 2014), and others reporting relatively consistent soil respiration values throughout the day (Davidson et al, 2000; Doughty & Goulden, 2008; Giardina & Ryan, 2002; Goulden et al, 2004; Litton et al, 2011; Salimon et al, 2004; Schwendenmann et al, 2003; Trumbore et al, 1995; Wood et al, 2013). The lack of significant variation of soil respiration at diel time scales in tropical forests could be a consequence of insufficient sampling frequency—a common limitation of soil respiration studies conducted in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…We found the month‐to‐month R S CV distribution to be relatively higher (median of 26%, Figure ) than the CV at shorter time scales. This is expected as months are disconnected from the predictable cyclic daily and annual temperature and moisture cycles that drive R S (Raich, ); but it has significant sampling implications given the popularity of monthly sampling. Our sampling requirement numbers (Table ) are largely consistent with the results of Jian, Steele, Thomas, Day, and Hodges (), who found (for deciduous forests, Table in that study) that 183 measurements were required to be 95% certain of being within 10% of the true mean, and 9 measurements to be 80% certain of being within 30%.…”
Section: Discussionmentioning
confidence: 99%
“…Fluxes were calculated based on the final 100 s of the 120-s measurement period as in Valverde-Barrantes et al (2007). Previous studies in these plots indicated that there was no meaningful diel variation in soil respiration (Raich 2017). Nevertheless, the order of measurements was changed at every sample time.…”
Section: Soilmentioning
confidence: 99%